Mastering panel metrics: Causal impact of democracy on growth - Shuowen Chen; Victor Chernozhukov; Iván Fernández-Val (Centre for Microdata Methods and Practice (cemmap), 2019)
The relationship between democracy and economic growth is of long standing interest. We revisit the panel data analysis of this relationship by Acemoglu et al. (forthcoming) using state of the art econometric methods. We argue that this and lots of other panel data settings in economics are in fact high-dimensional, resulting in principal estimators - the fixed effects (FE) and Arellano-Bond (AB) estimators - to be biased to the degree that invalidates statistical inference. We can however remove these biases by using simple analytical and sample-splitting methods, and thereby restore valid statistical inference. We find that the debiased FE and AB estimators produce substantially higher esti-mates of the long-run effect of democracy on growth, providing even stronger support for the key hypothesis in Acemoglu et al. (forthcoming). Given the ubiquitous nature of panel data, we conclude that the use of debiased panel data estimators should substantially improve the quality of empirical inference in economics.
Keywords: 330